Peningkatan Efesiensi Dan Kualitas Asuransi Umum Syariah Pada Sun Life Insurance di PT. Sun Life Syariah Cabang Medan - Irna Ardilla; Seri Handayani; Nurjannah Nurjannah; Rahmi Syahriza (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
In igeneral, iinsurance iis ihanding iover irisk iprotection ito ithe iinsurer, inamely ithe iinsurance icompany iand ithe iagreement iagreed iupon iwithin ia icertain iperiod. iPT. iSun ilife isharia iMedan ibranch iis ia igeneral isharia iinsurance icompany ilocated ion iJl. iCaptain iJumhana ino. i127, iSukaramai iII, ikec. iMedan iarea, iMedan icity, iNorth iSumatra. iThe iaim iof ithe iresearch iis ito ifind iout ihow ito iimprove ithe iefficiency iand iquality iof isuperior iproducts iof isharia igeneral iinsurance iat iPT. iSun ilife isharia ifield ibranch. iThe iresearch imethod iuses iqualitative imethods. iThe iresults iof ithe istudy, ithe ilevel iof iefficiency iof ia icompany iis inot idetermined iby ithe iamount iof itotal iincome, itotal iexpenses, ior itotal icapital iowned iby ithe icompany, iaccording ito iresearch ifindings iby. iHowever, ithe iability iof ia ibusiness ito imaximize iprofits ithrough ithe ieffective iuse iof iits iown iresources idetermines ithe ilevel iof iefficiency. iFor ithis ireason, iit ican ibe iconcluded ithat ithe iMedan iBranch iof iSun iLife iFinancial iSyariah ihas ibetter imanagement iskills ithan itraditional iinsurance icompanies iin idesigning iproducts ioptimally iand iminimizing ithe icosts irequired